Answer:
Option B
Step-by-step explanation:
Given that:
![\begin{gathered} y=x^2+3x-5 \\ y=x+3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/xo2uxsf55r9twehsh4vrwguyw0dr862fvp.png)
Since the right hand side of both equations are same, equate the left hand side of both the equations.
![\begin{gathered} x^2+3x-5=x+3 \\ x^2+2x-8=0 \\ (x+4)(x-2)=0 \\ x=-4,2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/p3y2i507a8yhtbu2vbzzieox0eby65e4rr.png)
The values of x are -4 and 2.
Substitute the values of x into the equation y = x+3.
When x = -4,
![\begin{gathered} y=-4+3 \\ =-1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/myrp66fe6ld1io8g548z11uwo8uqtxj1vq.png)
When x = 2,
![\begin{gathered} y=2+3 \\ =5 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/y8opl77t9hcrqm8jlc6x85p9qv49s21875.png)
y takes the values -1 and 5. Since -1 is less than 5, the smallest value of y is -1.
So, option B is correct.